2007
DOI: 10.1089/thy.2007.0261
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Roles of IFN-γ in Murine Models of Autoimmune Thyroid Diseases

Abstract: Interferon-gamma (IFN-gamma), a prototypic proinflammatory cytokine produced by several different cell types, including the Th1 subset of CD4(+) T cells, plays an important role in inflammation and autoimmune diseases. This review focuses on the varied and often contrasting roles of IFN-gamma in three murine models of autoimmune thyroid disease, experimentally induced autoimmune thyroiditis, the model of iodine-induced spontaneous autoimmune thyroiditis in NOD.H-2h4 mice and several different murine models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…IFN- γ, a prototypic proinflammatory cytokine produced by several different cell types, including the Th1 subset of CD4(+) T cells, plays an important role in inflammation and autoimmune diseases [13]. Carella C et al observed that INF- γ is the cytokine most clearly associated with AITD, especially hypothyroidism, despite being neither Th1- nor Th2-dependent [14].…”
Section: Discussionmentioning
confidence: 99%
“…IFN- γ, a prototypic proinflammatory cytokine produced by several different cell types, including the Th1 subset of CD4(+) T cells, plays an important role in inflammation and autoimmune diseases [13]. Carella C et al observed that INF- γ is the cytokine most clearly associated with AITD, especially hypothyroidism, despite being neither Th1- nor Th2-dependent [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Lxs, there are a host of other soluble mediators and cells central to resolution whose expression/synthesis occurs at strategic checkpoints throughout inflammation to switch the response off and restore homeostasis (12)(13)(14)(15)(16)(17). Although the sequential activation of these proresolution pathways has almost exclusively been elucidated using inbred rodents, little is known about their role in limiting inflammatory responses in humans.…”
mentioning
confidence: 99%
“…In other experiments using lung epithelia, activation of inducible nitric oxide (NO) synthase (iNOS) by IRF-1 led to a subsequent NO-induced activation of CFTR (12,36). IFN␥ has been implicated in the pathogenesis of a number of inflammatory diseases of infectious or presumed autoimmune origin (13,19,74). In the eye, IFN␥ has been detected in vitreous aspirates of patients with uveitis, proliferative vitreoretinopathy, and other inflammatory ocular diseases (21,26,40,51).…”
mentioning
confidence: 99%